ARTIFICIAL INTELLIGENCE IN ADULT ACADEMIC WRITING: EFFECTS ON WRITING QUALITY AND COGNITIVE AUTHENTICITY - Sri Nurhayati; Safuri Musa; Taufikin Taufikin (Nurul Jadid University, 2026)
The integration of artificial intelligence (AI) in adult academic writing is rapidly transforming how adult students produce, organize, and evaluate written work. This study examines how AI use affects text structure quality and cognitive authenticity, with attention to metacognitive self-regulation and ethical awareness. A mixed-methods approach was employed, combining survey data, pre–post writing comparisons, regression analysis, and qualitative interviews. The findings reveal that artificial intelligence significantly improves text structure quality by enhancing coherence, organization, and linguistic accuracy. The improvement is accompanied by a decline in cognitive authenticity, reflected in reduced originality, weaker authorial voice, and lower reflective depth. Regression results indicate that artificial intelligence engagement positively predicts structural quality but negatively affects authenticity. In contrast, metacognitive self-regulation, and ethical awareness function as protective factors, supporting both critical engagement and intellectual ownership. Qualitative findings further confirm that adult students experience artificial intelligence as both a structural support and a source of cognitive dependency.